Histopathology of body art revisited – analysis and discussion of 19 cases. (29th August 2013) - Körner, Rebecca; Pföhler, Claudia; Vogt, Thomas; Müller, Cornelia S. L.
Summary Background and Objectives With the number of tattoos increasing, a rising number of complications have also been reported, such as allergic and foreign body reactions or the development of malignant tumors. We discuss 19 patients with alterations in skin tattoos, define clinicopathologic characteristics and give a brief review of the literature. Patients and Methods Biopsy specimens were obtained in 13 of 19 patients. In all cases, staining was performed with hematoxylin‐eosin, periodic acid‐Schiff, CD68, CD123, and CD163. The inflammatory infiltrate was classified according to the pattern analysis of Ackerman. Results Three of 19 patients (15.8%) had temporary tattoos with henna and 16 (84.2%) had permanent tattoos. Histologically, among the 13 biopsy specimens we found signs of acute contact dermatitis in 2 (15.3%), lupus‐like patterns in 2 (15.3%), foreign body dermatitis in 5 (38.4%), deposition of pigment without inflammation or simple scarring in 2 (15.3%), and tumors in 2 patients (15.2%), 1 of which was a malignant melanoma. Conclusions Clinical presentation frequently, but not always, correlates with the histologic pattern. Obtaining a biopsy can be helpful in determining further investigations, for example allergy testing or a search for systemic involvement in cases of tattoo sarcoidosis.